Strategic implementation of deep learning curriculum in early childhood using the TQM framework - Alifia Arif Maulidya; Achmad Supriyanto (Universitas Muhammadiyah Malang, 2025)
The lack of structured strategic guidance for implementing a Total Quality Management (TQM)-based deep learning curriculum is a major obstacle in efforts to sustainably improve the quality of early childhood education. This study aims to analyze the implementation of an action plan within the deep learning curriculum program based on TQM in early childhood education. The research employs a qualitative approach with applied research methodology. Data was collected through unstructurred interviews, observations, and documentation with 52 respondents in RA Baipas and TK Firdaus at Malang City. Data validity is tested using source triangulation and analyzed using the Miles and Huberman model, consisting of data reduction, data display, and verification. The result of this study is the development of an action plan that can serve as a guideline for early childhood education institutions in implementing a TQM-based deep learning curriculum to enhance the quality of early childhood education sustainably.